2017
DOI: 10.1016/j.foodchem.2017.02.125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytosanitary irradiation on the postharvest quality of Seedless Kishu mandarins (Citrus kinokuni mukakukishu)

Abstract: Transnational trade of 'Seedless Kishu' mandarins (Citrus kinokuni mukakukishu) would require them to be subjected to a suitable phytosanitary treatment. Irradiation is used as an effective treatment for many fruit, but the effect on quality of kishu mandarins is unknown. 'Seedless Kishu' mandarins were treated with gamma irradiation (150, 400, and 1000Gy) and stored for three weeks at 6°C and then for one week at 20°C. Irradiation at 400 and 1000Gy promoted browning of the calyx end and fungal infection. Irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 39 publications
(52 reference statements)
2
10
0
Order By: Relevance
“…In fruit from top layer, 337 sucrose content tended to decrease with the irradiation dose while glucose and 338 fructose increased (P<0.05). Similar results were reported for mandarins treated with 339 0.15, 0.4 and kGy (Ornelas-Paz et al 2017). However, irradiation caused a different alteration of sugar content in fruit in the bottom layer, where a slight decreasing trend was observed for glucose and fructose while sucrose content was not altered significantly (P>0.05) (Fig.…”
Section: Total Soluble Solids (Tss) and Sugarssupporting
confidence: 86%
“…In fruit from top layer, 337 sucrose content tended to decrease with the irradiation dose while glucose and 338 fructose increased (P<0.05). Similar results were reported for mandarins treated with 339 0.15, 0.4 and kGy (Ornelas-Paz et al 2017). However, irradiation caused a different alteration of sugar content in fruit in the bottom layer, where a slight decreasing trend was observed for glucose and fructose while sucrose content was not altered significantly (P>0.05) (Fig.…”
Section: Total Soluble Solids (Tss) and Sugarssupporting
confidence: 86%
“…The other recent study reported that irradiation is not suitable for mandarins as it deteriorates their postharvest quality (for example firmness, sugars, and carotenoids). However, irradiation positively affected the content of most organic acids (Ornelas‐Paz and others ).…”
Section: Food Safety: Preservation By Microbial Inactivation and Hygimentioning
confidence: 97%
“…8 Moreover, some varieties of Citrus are not tolerant to irradiation treatment, which limits this potential of this method for quarantine treatment. 9 Compared with the abovementioned measures, fumigation is faster and more convenient. The US Department of Agriculture (USDA) established a 4-h fumigation schedule with 32 g m −3 MB at 21.1 ∘ C to disinfest B. dorsalis from avocado fruits (T101-c-1).…”
Section: Introductionmentioning
confidence: 99%
“…For phytosanitary irradiation, although its efficacy has been confirmed by several previous studies, its commercial adoption was restricted by regulatory issues and slow consumer acceptance . Moreover, some varieties of Citrus are not tolerant to irradiation treatment, which limits this potential of this method for quarantine treatment …”
Section: Introductionmentioning
confidence: 99%